Code of practice for project management for construction and development. (John Wiley, 2014)
The first edition of the Code of Practice for Project Management for Construction and Development, published in 1992, was groundbreaking in many ways. Now in its fifth edition, prepared by a multi-institute task force coordinated by the CIOB and including representatives from RICS, RIBA, ICE, APM and CIC, it continues to be the authoritative guide and reference to the principles and practice of project management in construction and development. Good project management in construction relies on balancing the key constraints of time, quality and cost in the context of building f.